LEGAL RESPONSIBILITY OF NOTARY DEEDS FOR ELECTRONIC ARCHIVES - Ani Muhammad Syuaib; Imam Abdi Utama; Teresa Irene Sumartono; Haryono Haryono; Mucharoroh Mucharoroh (UNISSULA, 2021)
Deeds made by notaries as public officials are authentic deeds in accordance with the formulation of Article 1 point (7) of the Law on Notary Office, that notary deeds are authentic deeds made by or before a notary according to the form and procedure stipulated by law. The approach method in this research is juridical normative. Based on the results of data analysis, it can be concluded that the use of electronic archives at least notary deeds has not yet obtained a strong legal basis, so it does not guarantee legal certainty. Legal certainty can be achieved, if there are no provisions that conflict between one law and another. The legal substance in the use of electronic records, at least notary deeds, has not been fully accommodated in the notary office law with the obligation to read the deed in front of witnesses and not meeting these requirements will result in legal sanctions for notaries. the law on information and electronic transactions which is the legal basis for notaries also does not provide an opportunity for electronic deeds by providing limits on notary deeds that are not included in electronic documents / information, so that they cannot be used as valid evidence.